2016
DOI: 10.1002/jbmr.2802
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Effect of Vitamin D Supplementation on Musculoskeletal Parameters in Adolescents One Year After Trial Completion

Abstract: We showed a beneficial effect of vitamin D supplementation on musculoskeletal parameters in adolescent girls in a 1-year, randomized, double-blinded placebo-controlled trial (RCT). Our objective for this study was to investigate the residual effect of vitamin D supplementation on bone mineral content (BMC), bone mineral density (BMD), at the lumbar spine and hip, lean mass, and height, 1 year after trial completion. We performed post hoc analyses in 167 adolescents, 86 girls and 81 boys, age 13.9 AE 2 years, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…While supplementation in boys did not yield any significant effect [42], low and high vitamin D doses resulted in a significant improvement in lean mass and total hip bone mineral content (BMC) in girls [24]; interestingly, this effect persisted after 1 year of discontinuation of trial supplementation [43]. Bone specific alkaline phosphatase (BAP) was assessed in 2 studies in children and adolescents [27, 28], falling into 2 different comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…While supplementation in boys did not yield any significant effect [42], low and high vitamin D doses resulted in a significant improvement in lean mass and total hip bone mineral content (BMC) in girls [24]; interestingly, this effect persisted after 1 year of discontinuation of trial supplementation [43]. Bone specific alkaline phosphatase (BAP) was assessed in 2 studies in children and adolescents [27, 28], falling into 2 different comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated substantial improvements in body lean mass and total hip bone mineral content (BMC), in girls only, both in the low dose (400 IU/d) and the high dose (2000 IU/d) arms, compared to placebo, and in total hip area, in the high dose group only ( El-Hajj Fuleihan et al, 2006 ). Interestingly, the latter effect persisted at 1 year after the discontinuation of the intervention ( Ghazal et al, 2016 ). The risk of bias in these trials varied widely ( Chakhtoura et al, 2017b ).…”
Section: Randomized Trials Of Vitamin D Supplementation In Different mentioning
confidence: 99%
“…In 2016, SACN and EFSA revised dietary reference values for vitamin D reporting an increased risk of adverse musculoskeletal health outcomes at serum 25(OH)D levels in the range of deficiency, but with different thresholds (< 10 ng/ml and < 20 ng/ml, respectively) [ 25 , 26 ]. Interestingly, a recent study showed that the beneficial effect of vitamin D on hip bone mass in Lebanese adolescent girls persisted 1 year after discontinuation of supplementation [ 226 ]. At present, some unanswered questions remain [critical times during which supplementation may be most effective, regimen and length of supplementation (continuous or intermittent), gender difference] [ 227 ], thus vitamin D supplementation to optimize bone mass acquisition should be reserved for children at risk for deficiency.…”
Section: Skeletal Actions Of Vitamin Dmentioning
confidence: 99%